2018
DOI: 10.1093/tbm/iby076
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual model of social networks and mechanisms of cancer mortality, and potential strategies to improve survival: an invited commentary

Abstract: In this article, the importance of social factors for cancer survivorship has been theoretically considered and empirically studied. This commentary and Kroenke's narrative review highlight how social network theory and methods may innovatively expand this substantive body of work. First, we add to a new understanding of cancer survivorship through: (a) discussing the delineation and differences between multiple social factors of interest across existing conceptual models; (b) characterizing their relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
(102 reference statements)
1
3
0
Order By: Relevance
“…Our findings contribute to growing research on the feasibility of network-based models for equity in cancer prevention and control [42,43,48]. Training 120 CHWs resulted in the successful reach of 1499 community members within less than a year, in line with past research on CHWs and navigators [46,47]. Our findings further suggested that CHWs and navigators can empower residents to become change agents themselves.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our findings contribute to growing research on the feasibility of network-based models for equity in cancer prevention and control [42,43,48]. Training 120 CHWs resulted in the successful reach of 1499 community members within less than a year, in line with past research on CHWs and navigators [46,47]. Our findings further suggested that CHWs and navigators can empower residents to become change agents themselves.…”
Section: Discussionsupporting
confidence: 84%
“…Successful information transfer reflects both the quality of learning by the community member and the specificity of the message that they will share as a change agent. High information transfer thus may lead residents to use information for themselves and to diffuse high-quality messages throughout their networks [46][47][48][49]. While promising, these conceptual mechanisms may depend on various factors.…”
Section: Introductionmentioning
confidence: 99%
“…An additional limitation to the underestimation of intervention efficacy is the failure to measure “spillover effects.” This includes changes in BC communication and behavior among nonparticipants who are connected to participants. Simultaneous measurement of direct intervention effects (i.e., participant behaviors) and spillover effects (i.e., network members’ behaviors) can be useful for more precise, comprehensive estimates of intervention efficacy (Benjamin-Chung et al, 2015; El-Sayed et al, 2012; Molina, 2018; Valente & Pitts, 2017).…”
mentioning
confidence: 99%
“…We consider these factors in terms of family/friend informal caregivers. First, family/friend informal caregivers may not necessarily provide the cancer-specific support necessary to buffer cancer-related debt and other stressors (e.g., knowledge of financial assistance programs) when compared to health care providers and more peripheral network members (e.g., new peer survivor acquaintances; Arora et al 2007; Kroenke 2018; Molina 2018; Molina et al 2016). Second, family and friends provide cancer-related caregiving in the context of affectively close relationships, long-term relationships, and normative expectations of family responsibility for care (Jacobs et al 2016; Keating et al 2003; Litwin and Auslander 1990).…”
Section: Introductionmentioning
confidence: 99%